ANALISIS DISKRIPSI PENCEMARAN AIR SUMUR PADA DAERAH INDUSTRI PENGECORAN LOGAM - Susanto, Joko Prayitno (Jurnal Teknologi Lingkungan, 2005)
The objective of the study is to explain the ground water impact of foundry industry activities in Ceper, Klaten Regency, Central Java Province. The result of this study shows that the tendency of some metal parameters (Fe, Mn and Pb) increases at water taken from some location artesian well or traditional well.Slags do not manage yet very well supposition ally causing the pollutant so that’s created opportunity to bring about the process leaching by the rain toward the inside metal components. Recommendation : In the future, the anticipate to expantion this industry is the slag manage very well through utilization exact and friendly environment technology.